A STUDY ON CONCEPTION RATES IN MARES SERVICED AT FIRST POSTPARTUM HEAT - Fathalla, M.; Younis, L.; M.A. Jawad, N. (The Iraqi Journal of Veterinary Medicine, 1990)
It is a custom among among horse breeders in Iraq to service the mares at first pastpartum heat (foal heat) Conception rates following such services were reported to reach 50%. Therefore, attempts were made to investigate the conception rates of first postpartum service in mares. The study was conducted on 32 Arabian mares aged between 8-12 years located at Al-Frosia stables in Abu-Ghraib. All mares were serviced at their foaling heat and were examined for pregnancy 4-6 months after the service. The results of the pregnancy examination revealed that only 9 mares (28%) were pregnant. This low percentage of conception rates might be due to incomplete uterine involution. Therefore, we recommend service at foal heat free from parturient complications.